Refusal and rupture as a postdramatic revolt : an analysis of selected South African contemporary devised performances with particular focus on works by First Physical Theatre Company and the Rhodes University Drama Department - Haxton, Robert Peter (Rhodes University, Faculty of Humanities, Department of Drama, 2014)
This mini-thesis investigates the concepts of refusal and rupture as a postdramatic revolt and how these terms can be applied and read within the context of analysing contemporary devised performance in South Africa. The argument focuses on the efficacy of Hans-Thies Lehmann's postdramatic terminology and the potential of its use in an appreciation of contemporary performance analysis. I investigate the potential in South African contemporary devised performance practice to challenge prevailing modes of traditional dramatic expectation in order to restore the experience of discovery and questioning in the spectator. This research is approached through a qualitative process which entails a reading and application of selected critical texts to the analysis with an application of Lehmann's terminology. This reading/application is engaged in a dialogue with the interpretative and experiential aspects of selected South African devised performances with particular focus on four cross-disciplinary works selected for analysis. Chapter One functions as an introduction to the concept of postdramatic theatre and the application of the terms refusal and rupture as deconstructive keywords in the process of a devised performance. Chapter Two is an analysis of several South African contemporary performances with particular focus on Body of Evidence (2009) by Siwela Sonke Dance Company, Wreckage (2011) a collaboration by Ubom! Eastern Cape Drama Company and First Physical Theatre Company, Discharge (2012) by First Physical Theatre Company, and Drifting (2013) by The Rhodes University Drama Department. This mini-thesis concludes with the idea that with an understanding of refusal and rupture in a postdramatic revolt, contemporary devised performance achieves an awakening in its spectators by deconstructing the expectation of understanding and the need for resolve; the assumption and need for traditional dramatic structures and rules are challenged. Instead, it awakes an experience of discovery and questioning.
Keywords: Lehmann, Hans-Thies -- Postdramatisches Theater -- English; Rhodes University -- Department of Drama; First Physical Theatre Company; Experimental theater -- South Africa; Experimental theater -- History and criticism; Performance art -- South Africa; Performance art -- History and criticism